Pedagogical Competence of Al-Qur’an Hadith Teachers in Improving Students Al-Qur’an Reading Skills (Case Study at State Islamic Junior High School 1 West Tanjung Jabung) - Nabila Nabila; Musli Musli; Muhammad Qodri (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the pedagogical competence of Al-Qur'an Hadith teachers in improving students Al-Qur’an reading skills at State Islamic Junior High School 1 West Tanjung Jabung using a descriptive qualitative approach. The results indicate that teachers pedagogical competence is quite good, but still needs improvement in aspects of learning management and media utilization. Students Al-Qur’an reading skills are influenced by family, student, and madrasah environmental factors. Efforts to improve this are carried out through MGMP (Student Group Leadership Group), teacher training, Al-Qur’an reading habituation, and provision of learning facilities.